2004
DOI: 10.1099/ijs.0.63090-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome reduction in prokaryotic obligatory intracellular parasites of humans: a comparative analysis

Abstract: Obligatory intracellular parasites have undergone significant genome reduction by gene loss over time in the context of their obligate associations with the host. The flux, streamlining and elimination of genes in these genomes constitute a selective and ongoing process. Comparative analyses of five completely sequenced obligatory intracellular parasite genomes reveal that these genomes display marked similarities in patterns of protein length and frequency distribution, with substantial sharing of a 'backbone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 18 publications
2
46
0
1
Order By: Relevance
“…Consistent with other obligate intracellular bacteria (3,23,55,84), and as proposed by Seshadri et al (63), our results suggest that the C. burnetii genome is undergoing reductive evolution. Accordingly, we found very few polymorphisms resulting from DNA insertion.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with other obligate intracellular bacteria (3,23,55,84), and as proposed by Seshadri et al (63), our results suggest that the C. burnetii genome is undergoing reductive evolution. Accordingly, we found very few polymorphisms resulting from DNA insertion.…”
Section: Discussionsupporting
confidence: 80%
“…Analysis of coding ORFs indicates that, although C. burnetii shares similarities in lifestyle and parasitic strategies to other obligate intracellular bacteria, it generally differs considerably with respect to genome size, metabolic and transporter capabilities, the presence of mobile genetic elements, and the extent of genome reduction (23,55,57,63,84). To further define the genetic diversity of C. burnetii, gDNA of 24 isolates of diverse geographical and environmental origins were hybridized to a custom Affymetrix microarray chip (RMLchip_a) containing probe sets corresponding to all ORFs of the NMI isolate.…”
mentioning
confidence: 99%
“…Besides the lack of biosynthesis, several nutrient transporters that are not found in any other crenarchaeote are present in T. pendens. A lack of biosynthetic ability and an increase in nutrient transport ability are features commonly found in obligate parasites (49). However, T. pendens lacks other features of obligate intracellular parasites, such as a reduced genome size (40,62), a loss of signal transduction and DNA repair proteins (36), an increased percentage of A ⅐ T base pairs (35,62), and a decreased number of fusion proteins (K. Mavromatis and N. C. Kyrpides, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Sakharkar et al [12] reported that throughout evolution, genes that once played major roles are eventually discarded because they are no longer under selective pressure. Genome stability is therefore achieved by the loss of selected groups of proteins involved in genome dynamics and gene mobility [12]. Gene degradation targets overlapping subsets of potentially dispensable genes while adapting to the selective pressures of different niches [13].…”
Section: Genomics In Understanding Host-specifi C Adaptations and Genmentioning
confidence: 99%
“…In efforts to characterize the evolutionary forces underlying genome reduction and to understand the dynamics of microbial genomes, a critical issue concerns the size, content and processes of deletions [12]. The reduction in genome size of obligatory intracellular parasites results in genome stability via loss of selected groups of proteins, e.g.…”
Section: Genomics In Understanding Host-specifi C Adaptations and Genmentioning
confidence: 99%